Papuamicrus gen. n., a new genus of Cephenniini from New Guinea (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
A new genus of Cephenniini, Papuamicrus gen. n. (type species Papuamicrus globosus sp. n.) is described based on specimens collected in Papua New Guinea. The new genus belongs to the ‘Cephennomicrus group’ of genera and is characterized by a highly ‘reductive morphology’ of the dorsum, lacking pronotal pits and elytral foveae, but having uniquely shaped prosternal and mesoventral processes and a highly unusual for Cephenniini aedeagal structure with a basal lentiform sclerotization situated at middle of a small diaphragm shifted to the basal surface of the median lobe. Updated identification key to the world genera of Cephenniini is given to accommodate the new taxon.